Analisa Efisiensi Energi pada Proses Produksi Obat X di Perusahaan YZ - M. Samsuri; Hernowo Widodo; Ananda Siti Choirunnisa (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Drugs are chemicals that are produced to reduce pain and prevent the risk of various diseases. In the manufacture of drugs, several stages of the process are needed which are quite long and require calculations from each process to produce products that meet the requirements and minimize errors during the process that can cause company losses. The research was carried out by direct observation during the process as well as collecting data on the mass of materials before and after the process, as well as critical parameters listed from the PPI (Main Processing Procedure) book for 1 batch of drug manufacture which takes more than 24 hours to manufacture. From observations, it is known that the drug manufacturing process has an adiabatic process where the resulting mass balance has the equation mass in = mass out and there is no chemical reaction that takes place. In the drying process, the heat balance can be calculated because this process produces heat which requires a certain amount of energy in the process. The drying machine used is an FBD (Fluidized Bed Dryer) machine which requires a certain amount of power so that the efficiency of this machine can be known to maximize the process.